The effect of motor overflow on bimanual asymmetric force coordination - Cunningham, David A.; Roelle, Sarah M.; Allexandre, Didier; Potter-Baker, Kelsey A.; Sankarasubramanian, Vishwanath; Knutson, Jayme S.; Yue, Guang H.; Machado, Andre G.; Plow, Ela B. (Experimental brain research, 2017)
Motor overflow, typically described in the context of unimanual movements, refers to the natural tendency for a ‘resting’ limb to move during movement of the opposite limb and is thought to be influenced by inter-hemispheric interactions and intra-cortical networks within the ‘resting’ hemisphere. It is currently unknown, however, how motor overflow contributes to asymmetric force coordination task accuracy, referred to as bimanual interference, as there is need to generate unequal forces and corticospinal output for each limb. Here, we assessed motor overflow via motor evoked potentials (MEPs) and the regulation of motor overflow via inter-hemispheric inhibition (IHI) and short-intra-cortical inhibition (SICI) using transcranial magnetic stimulation in the presence of unimanual and bimanual isometric force production. All outcomes were measured in the left first dorsal interosseous (test hand) muscle, which maintained 30% maximal voluntary contraction (MVC), while the right hand (conditioning hand) was maintained at rest, 10, 30, or 70% of its MVC. We have found that as higher forces are generated with the conditioning hand, MEP amplitudes at the active test hand decreased and inter-hemispheric inhibition increased, suggesting reduced motor overflow in the presence of bimanual asymmetric forces. Furthermore, we found that subjects with less motor overflow (i.e., reduced MEP amplitudes in the test hemisphere) demonstrated poorer accuracy in maintaining 30% MVC across all conditions. These findings suggest that motor overflow may serve as an adaptive substrate to support bimanual asymmetric force coordination.